Współczesne postulaty unowocześnienia Kościoła i ich relewancja - Hajduk, Ryszard (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Nowadays, the Catholic Church is often the subject of severe criticism. It is accused of being an anachronism, ossificating of organizational structures, limiting freedom of speech, propagating outdated life patterns and pre-scientific culture, totalitarianism and greed. The Church’s critics also formulate demands for its renewal, calling for the modernization of structures, the redefinition of ecclesiastic doctrine, the refinement of the communication of the content of faith and the adaptation of activities to social expectations. B y indicating the Church the directions of transformation, they refer to current trendy (philosophical) views and social processes taking place in human reality. They also ignore the fact that the Church is “God’s building” and that it cannot be reformed without reference to the Word of God and tradition. The Church can truly be renewed only by the power of the Gospel and by faithfulness to the mission entrusted to him by Jesus Christ.